The Biography of Muhammad the issue of the sources - Motzki, Harald (Islamic history and civilization, 2000)
This collection of articles presents the most recent methodological developments in the study of the life of Muhammad and highlights the improvement of its material-basis due to sources which have only recently become available or which have been neglected.